Foreign Policy of the USA and Russia in East Asia - Anna Corsaro; Daniel Djouder (Сравнительная политика, 2015)
his paper analyzes the role of the Russian Federation as a world power in the East Asian area between 2000 and 2010, delving into its relations with major regional actors, namely: China, Japan, Taiwan, North Korea and South Korea. Russia’s policies and actions are compared to those of the United States as the arguably predominant superpower during most of the period in exam. Emphasis is put on the possible causes of escalation between the various actors within the Asian scenario, with a detailed comparison between the actions taken by Russia and the United States.